Monostotic fibrous dysplasia of fibula: a rare case report - Sil, Bhupes; V., Naveen; Roy, Dipen (International Journal of Research in Orthopaedics, 2021)
Fibrous dysplasia is a developmental anomaly of bone formation that may exist in monostotic or polyostotic form. Monostotic fibrous dysplasia of fibula is a rare case with unusual site and most common sites being facial bones, ribs, proximal femur and tibia. We report a case of 10-year-old boy attended our hospital with occasional pain in left leg while having strenuous activity. On clinical examination there was no obvious swelling with normal appearing skin. Radiographic examination revealed lesion with both radiopaque and radiolucent features showing a “ground-glass” appearing lesion in proximal one third of fibula. Differential diagnosis considered are simple bone cyst, non-ossifying fibroma, osteo-fibrous dysplasia, adamantinoma. As a definitive treatment curettage was done and biopsy sent for histopathological examination, which confirmed he diagnosis. Follow up after 10 months shows normal bone growth as evidenced radiologically and patient is asymptomatic. Case in detail and recent review of literature has been discussed. From our case, we have shown that it is possible to treat uncomplicated fibrous dysplasia with minimally invasive approach of simple curettage. Patient is symptomatically relieved within 2 months without any complications.